Wrist extensor muscle activity is less task-dependent than wrist flexor muscle activity while simultaneously performing moderate-to-high handgrip and wrist forces. Issue 12 (2nd December 2021) - Forman, Davis A.; Forman, Garrick N.; Holmes, Michael W. R.
Abstract: The aim of this study was to characterise wrist extensor and flexor muscle activity during combinations of moderate-to-high handgrip and wrist forces that are similar to actions and intensities used in many workplace settings. Surface electromyography was recorded from three wrist flexors and three wrist extensors while participants performed simultaneous handgrip forces and wrist forces ranging in intensities from 15% to 60% of maximum. While the wrist flexors were highly task-dependent, in that their activity significantly changed between conditions, wrist extensor activity was consistently high throughout the experiment. Wrist joint co-contraction was also significantly higher when the wrist extensors were functioning as the antagonists. These findings suggest that the wrist extensors likely demonstrate consistently higher muscleactivity during most tasks of the hand and wrist, which is likely a leading mechanism behind why they develop chronic overuse injuries more frequently than the wrist flexors. Practitioner Summary: This study was conducted to identify forearm muscle activity patterns that might help explain why the wrist extensors develop overuse injuries more frequently than the flexors. Results demonstrated that the wrist extensors are consistently, highly active during combined handgrip and wrist forces and exhibit no periods of low muscle activity. Abbreviations: BB: biceps brachii; ECR: extensor carpi radialis; ECU: extensor carpi ulnaris; ED: extensor digitorum; EMG: electromyography; ES: effect size; FCR: flexor carpi radialis; FCU: flexor carpi ulnaris; FDS: flexor digitorum superficialis; MVC: maximal voluntary contraction; MVE: maximal voluntary excitation; SD: standard deviation; SE: standard error; TB: triceps brachii